Antioxidant and anti-inflammatory action (in vivo and in vitro) from the trunk barks of Cabreúva (Myrocarpus frondosus Allemao, Fabaceae). (1st March 2021) - Bottamedi, Mariana; Pereira dos Santos Nascimento, Marcus Vinícius; Fratoni, Eduarda; Kinoshita Moon, Yeo Jim; Faqueti, Larissa; Tizziani, Tiago; Sandjo, Louis P.; Siminski, Alexandre; Dalmarco, Eduardo Monguilhott; Mendes, Beatriz Garcia
Abstract: Ethnopharmacological relevance: Myrocarpus frondosus, known as cabreúva, is a tree whose trunk barks are used in folk medicine as tea, syrup, ointments, and tinctures for the treatment of inflammation. However, there is no scientific evidence demonstrating this activity. Aim of the study: The present investigation was focused on evaluating the antioxidant and anti-inflammatory activities of M. frondosus, using the in vitro model of RAW 264.7 macrophages induced by LPS and the in vivo model of mouse pleurisy induced by carrageenan. Materials and methods: M. frondosus trunk barks were dried at room temperature for seven days and subjected to exhaustive maceration with ethanol (70%) to obtain its crude extract (CE). CE was subjected to UPLC-HRMS analysis to establish its chemical profile. Its antioxidant activity was evaluated using the DPPH method, reducing power by the iron (III) to iron (II) reduction assay and the β-carotene-linoleic acid bleaching assay. The RAW 264.7 macrophages were pretreated with the CE in a non-cytotoxic concentration and induced by LPS (1 μg/mL). After 24 h, using the supernatant, we evaluated the nitric oxide (NOx) and interleukin-6 (IL-6) levels. The anti-inflammatory effects of CE (at doses of 30, 100 and 300 mg/kg) were evaluated on leukocyte migration (total and differential), exudate concentrations, myeloperoxidase (MPO) and adenosine-deaminase (ADA) activities, NOx, tumor necrosis factor-α (TNF-α), and IL-6 levels, by using a murine model of neutrophilic inflammation. Results: The UPLC-HRMS of CE revealed the presence of isoflavonones, including biochanin A and formononetin. CE exhibited good antioxidant activity by quenching and decreasing free radicals, as well as reducing pro-oxidant metals. CE did not show cytotoxicity at a concentration below 11 μg/mL and reduced the secretion of the pro-inflammatory NOx in the inflamed macrophages. In vivo assay revealed that CE caused a pronounced inhibition on leukocyte migration, and this inhibition was due to its ability to reduce neutrophil migration. Moreover, CE was also able to reduce the release of critical pro-inflammatory mediators such as MPO, NOx, TNF-α, and IL-6. Conclusions: All these findings indicate that M. frondosus exhibited antioxidant activity and anti-inflammatory effect. Graphical abstract: Image 1